2016
DOI: 10.5152/tud.2016.63903
|View full text |Cite
|
Sign up to set email alerts
|

The histopathological evaluation of healing effects of vitamin C administered before methotrexate therapy on testicular injury induced by methotrexate

Abstract: Objective: Methotrexate (MTX) leads to acute toxic side effects in tissues or organs containing rapidly dividing cells such as seminiferous tubules. In this study, we investigated the protective effects of vitamin C against MTX-induced injury in rat testis. Material and methods:A total of 31 rats were divided into 4 groups, including the control group. The study was completed within 4 weeks and the rats received daily doses of 2 mL/kg SF, 100 mg/kg vitamin C and 10 mg/kg/day MTX i.p according to their groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…In our study, in accordance with literature, seminiferous tubule diameter 7,9-11,48 and germinal epithelial thickness 10,33 in the MTX group decreased significantly, while interstitial field width 34,50 increased significantly. Saxena et al 49 reported that MTX could not replicate the DNA of germinal epithelial cells and significantly decrease the seminiferous tubule cellular content by inhibiting DHFR, the essential enzyme required for DNA synthesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, in accordance with literature, seminiferous tubule diameter 7,9-11,48 and germinal epithelial thickness 10,33 in the MTX group decreased significantly, while interstitial field width 34,50 increased significantly. Saxena et al 49 reported that MTX could not replicate the DNA of germinal epithelial cells and significantly decrease the seminiferous tubule cellular content by inhibiting DHFR, the essential enzyme required for DNA synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…[6][7][8] It also causes testicular degeneration. [9][10][11][12] The exact mechanisms of MTX toxicity are still elusive. A well-known mechanism of MTX toxicity is the inhibition of dihydrofolate reductase (DHFR).…”
Section: Introductionmentioning
confidence: 99%
“…Blocking tetrahydrofolate synthesis by methotrexate stops cell division and protein synthesis. It is known that the cytotoxic effect of MTX on the 'S phase' of the cell cycle is a factor that inhibits cell division (3). Moreover, this cytotoxic effect is not limited to only tumor cells; MTX is known to affect vital organs through endogenous oxidant systems and inflammatory pathways (4).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this injury, destruction of the spermatogenic epithelium, changes in the support cell structure, and antioxidant enzyme activities can occur (Wang et al, 2018). Many studies show that the toxic effects of MTX on the testicles are reduced by the use of various antioxidant substances (Akacha et al, 2020; Felemban et al, 2020; Oufi & Al‐Shawi, 2014; Pınar et al, 2018; Sayılmaz et al, 2016; Wang et al, 2018; Yaman et al, 2018; Yuluǧ et al, 2013). Furthermore, omega‐3 fatty acids present in fish oil (FO) have been shown to protect rat testis tissue from oxidative damage (Qi et al, 2017; Uygur et al, 2014).…”
Section: Introductionmentioning
confidence: 99%